How China's "Later, Longer, Fewer" Campaign Extends Life Expectancy: A Study of Intergenerational Support for Elderly Parents - Cynthia Bansak; Eva Dziadula; Sophie Xuefei Wang (Institute of Labor Economics (IZA), 2024)
This study documents increased intergenerational support for elderly parents in China among adults who were exposed to the "Later, Longer, Fewer" (LLF) family planning campaign in the 1970s. Using the China Health and Retirement Longitudinal Study, we identify adults of childbearing age whose fertility was reduced. We find LLF exposure increases the likelihood of wife's parents residing in the same household. As expected in a patrilineal society, the increase in support is realized by the husband's parents through more visits and financial transfers. Supporting our findings of stronger social networks, LLF exposure significantly increases the elderly parent's age at death.
Keywords: H31; I31; J13; 330; fertility; China; "Later; Longer; Fewer" campaign; family planning; co-residency; intergenerational transfers; aging population